Somatic symptom disorder triggered by lifetime trauma: a case report - Siliézar-Marroquin, Ana Bárbara; López-Melgar, Ricardo (Journal of Physiotherapy in Mental Health, 2026)
Somatic Symptom Disorder (SSD) is characterized by persistent and distressing physical symptoms that cannot be fully explained by a medical condition. Cumulative lifetime trauma is a well established risk factor for SSD, often overlooked in traditional biomedical evaluations. Objective: To describe a complex case of SSD triggered by long standing psychological trauma and to highlight the diagnostic and therapeutic value of a trauma-informed, interdisciplinary approach. Materials and methods: A case of a 40-year-old Guatemalan woman with incapacitating chronic low back pain and multiple negative findings on structural and neurophysiological testing is presented. Her history revealed childhood physical abuse, a rape-related pregnancy, and prolonged intimate partner violence. Despite neurosurgical management, she reported a pain intensity of 9/10 on the Numeric Rating Scale (NRS), significant functional impairment, and depressive symptoms. A comprehensive psychiatric evaluation supported a diagnosis of SSD per DSM-5-TR criteria. She received psychoeducation, trauma-focused cognitive behavioral therapy, and graded physical rehabilitation. The rehabilitation program was designed and supervised by a licensed physiotherapist, focusing on progressive mobilization, core strength, and recovery of daily function. Results: After eight weeks of interdisciplinary treatment, the patient’s pain level decreased to 5/10 on the NRS, PHQ-9 scores dropped from 18 (moderately severe) to 8 (mild), and she experienced a marked improvement in mobility and daily functioning. Conclusions: This case underscores the importance of identifying trauma as a central component in chronic pain syndromes. SSD remains underdiagnosed in trauma exposed populations, particularly in low resource settings. Early psychiatric referral and integrated care can prevent unnecessary interventions and improve long term outcomes.